Las colecciones de arte en la Universidad de los Andes - Herrera, Alexander; Navas Sanz de Santamaría, Pablo, 1953- (Colección Catálogos, 2019)
This book is the first of the collectionCatálogos, a line of research on the cultural heritage of the Faculty of Arts and Humanities of the Universidad de los Andes. The texts reveal the heritage that is found in the university and investigates the history of the objects and artworks that are housed there, their material transfer and the imaginary. The four chapters, written by professors and students, range from prehispanic art collections to 20th century Colombian art.